Geulayang Maco: From Cultural Practice to Science Learning Praxis - Rita Sari; Maksudin Maksudin; Ibrahim Ibrahim; Sigit Prasetyo (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Science learning in elementary schools often remains conceptual and lacks a connection between scientific knowledge and students’ local cultural contexts. This study aims to describe the effectiveness of the Seuramoe Saentia learning model, grounded in the local culture of Geulayang Maco (Acehnese traditional kite), in improving students’ understanding of force and motion concepts in Grade IV of MIS Gampong Meutia. The research employed a quasi-experimental one-group pretest–posttest design. The subjects consisted of 33 students, and data were collected through observation sheets and five-item essay tests administered before and after the learning intervention. Data were analysed using descriptive statistics and normalised gain (N-Gain) to measure improvement. The results revealed an average N-Gain score of 0.69 (medium–high category), indicating that learning through the Geulayang Maco context effectively enhanced conceptual understanding of force and motion. The most dominant student activities occurred during the exploration and artefact creation stages, reflecting active engagement in linking cultural practices with scientific concepts. The findings imply that the insertion of local wisdom into science education is essential to strengthen scientific literacy, cultural character, and the contextual relevance of science learning in students’ daily lives